The analysis and assessment of risk factors in the visual lifestyle of teenagers from the perspective of myopia prevention a case study: SMK Dato' Sheikh Ahmad / Mohammad Hafshah Hasbullah, Nur Azlin Miswan and Siti Shafiqah Mohamed Zali - Hasbullah, Mohammad Hafshah; Miswan, Nur Azlin; Mohamed Zali, Siti Shafiqah (2019)
Myopia was one of the common refractive error in adolescent population. It was defined as near-sightedness caused by in an incongruity between the power of the optical clements of eyes and its axial length. In Malaysia, the increased in epidemic myopia among seven years old children was nine point eight percent to 34.4% by 15 years old. It showed that myopia became a major issues that arose among children in Malaysia. The study used primary data that had been collected from SMK Dato' Sheikh Ahmad, Serernban, Negeri Sembilan, Malaysia. This study was involved with 268 secondary students frorn both level of form (lower and upper form). A stratified sarnpling was performed to obtain a sample from the population at SMK Dato' Sheikh Ahmad. The purpose of this study was to determine the risk factors that affect the epidemic myopia among stude:its in Seremban. The factors were consists of gender, near work activities, rarcnt thm had myopia, outdoor activities and diet. This study also invistigate the difference between male and female students that had myopia and the characteristic of students that had myopia. There were 120 students had myopia while 148 students do not had myopia. Besides, there was a significant difference between female students who had myopia compared to male students. Using logistic regression analysis. this study found that factor gender, near work activities and parents that had myopia were significant to explain the epidemic of myopia while the others foctor were not significant.